2021
DOI: 10.1016/j.adro.2020.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Inverse Dose Planning After Yttrium-90 Selective Internal Radiation Therapy in Hepatocellular Cancer

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…2,3 The possibility of using combined therapies has also been recommended in the literature. 4,5 There is a large body of prospective and retrospective literature demonstrating both safety and efficacy of radioembolization for the management of primary 2,[6][7][8] and metastatic 3,9,10 liver cancers. The literature for colorectal liver metastases, especially patients with liver only, or liver dominant disease, is particularly extensive.…”
Section: Clinical Indications and Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 The possibility of using combined therapies has also been recommended in the literature. 4,5 There is a large body of prospective and retrospective literature demonstrating both safety and efficacy of radioembolization for the management of primary 2,[6][7][8] and metastatic 3,9,10 liver cancers. The literature for colorectal liver metastases, especially patients with liver only, or liver dominant disease, is particularly extensive.…”
Section: Clinical Indications and Patient Selectionmentioning
confidence: 99%
“…The therapeutic ratio effectively improves intrahepatic tumor control while minimizing the relative risk of radioembolization‐induced liver disease (REILD) even for patients with extensive tumor burden 2,3 . The possibility of using combined therapies has also been recommended in the literature 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…This approach was shown to be technically feasible in the treatment of hepatocellular cancer (HCC), where multiple intrahepatic tumours were targeted using yttrium-90 selective internal radiation therapy ([ 90 Y]Y-SIRT), which involves the administration of radiolabelled microspheres into the hepatic artery, combined with EBRT to bulk lesions. Two studies demonstrated methods for combining the absorbed dose from [ 90 Y]Y-SIRT with that of EBRT [12,13]. Using the biological effective dose (BED) which is a quantitative measure of the biological effect of a radiotherapy treatment taking into account dose per fraction or dose rate and total dose, it was possible to compute the combined dose from both sources (Figure 1).…”
Section: Spatial Co-operationmentioning
confidence: 99%
“…Liver is contoured in blue and tumour in magenta. Reproduced with permission from [12]. and rate of efflux from the tumour or normal organs.…”
Section: Radiobiological Considerationsmentioning
confidence: 99%
“…This information can be used to determine undertreated areas of tumor which may require additional therapy, such as a more selective TARE, SBRT, or other locoregional therapies. A recent study combining EBRT and SIRT utilizing y-90based dosimetry in 10 HCC patients appeared safe [66]. Further studies are needed regarding the safety and efficacy of TARE using these more advanced dosimetry methodologies.…”
Section: Sirt For Clmsmentioning
confidence: 99%